Accurate pose estimation using single marker single camera calibration system - Pati, Sarthak; Erat, Okan; Wang, Lejing; Weidert, Simon; Euler, Ekkehard; Navab, Nassir; Fallavollita, Pascal (Proceedings of SPIE - The International Society for Optical Engineering, 2013)
Visual marker based tracking is one of the most widely used tracking techniques in Augmented Reality (AR) applications. Generally, multiple square markers are needed to perform robust and accurate tracking. Various marker based methods for calibrating relative marker poses have already been proposed. However, the calibration accuracy of these methods relies on the order of the image sequence and pre-evaluation of pose-estimation errors, making the method offline. Several studies have shown that the accuracy of pose estimation for an individual square marker depends on camera distance and viewing angle. We propose a method to accurately model the error in the estimated pose and translation of a camera using a single marker via an online method based on the Scaled Unscented Transform (SUT). Thus, the pose estimation for each marker can be estimated with highly accurate calibration results independent of the order of image sequences compared to cases when this knowledge is not used. This removes the need for having multiple markers and an offline estimation system to calculate camera pose in an AR application. © 2013 SPIE.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Augmented reality; Kalman filter; Scaled unscented transform; Single marker calibration; Single marker tracking